A Cross-Check of the Reflectance Models to Be Used in Interpretation of Observations of Regolith-Like Surfaces - Tishkovets, Victor P.; Petrova, Elena V. (Frontiers in Remote Sensing, 2022)
Many current and proposed programs of satellite remote sensing of the Earth and other celestial bodies rely upon measurements of the intensity and polarization of light scattered by these bodies. These measurement data are interpreted by searching for the best fits to light-scattering characteristics precalculated with some theoretical models. For regolith-like surfaces, i.e., discrete densely packed random media, the light-scattering models are still under development and they work under different approaches. Here, to estimate the difference between the reflectance characteristics yielded by these procedures, we compare the results of simulations performed according to five frequently used approximate models of a semi-infinite particulate medium. Special attention is paid to taking into account the weak-localization effect. The models differ by the scattering matrixes of a volume element and the dependence of the imaginary part of the effective refractive index on the filling factor. The volume element is an individual spherical particle or a randomly oriented cluster of particles. The cases of modifying the scattering matrix by the static structure factor correction or by subtracting the contribution of the mean field are also considered. The values for the size parameter of particles or monomers in the clusters and the refractive index were assumed at 1.76 and 1.50 + i0.0001, respectively; and two values for the filling factor of the medium (defined as a volume fraction occupied by particles in the medium), 20 and 10%, were considered. Our analysis shows that the angular dependences of the normalized intensity and the linear polarization degree obtained with the considered models of a semi-infinite discrete medium are rather close to each other. Moreover, the results of modeling with accounting for the dependence of the imaginary part of the effective refractive index on the filling factor, which is typical of a nonsparse medium, are in good agreement with the corresponding characteristics for a large cloud of particles (N is equal to or exceeds 106) with the filling factor up to 20%, which were obtained by approximate numerical methods but well follow the trends found in rigorous simulations for somewhat smaller ensembles of particles (Penttilä et al., JQSRT, 2021)